The Influence of Digital Literacy, Technology Adoption, and Innovation Capability on MSME Business Performance - Ikhwatun Hasanah; Reza Fauzi Nazar; Muhamad Sigid Safarudin; Noorhani Dyani Laksmi (Malaqbi Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in economic growth, employment generation, and business development. However, the rapid advancement of digital technologies and increasing market competition require MSMEs to enhance their capabilities to remain competitive and sustainable. This study aims to examine the influence of digital literacy, technology adoption, and innovation capability on MSME business performance. The study employs a quantitative research approach using a cross-sectional survey design. Data were collected from 200 MSME owners and managers through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital literacy, technology adoption, and innovation capability have positive and significant effects on MSME business performance. Digital literacy enables MSME owners to effectively utilize digital technologies and improve decision-making processes. Technology adoption contributes to operational efficiency, broader market access, and enhanced customer engagement. Meanwhile, innovation capability demonstrates the strongest influence on business performance, indicating that MSMEs with greater abilities to develop new products, services, and business processes achieve superior business outcomes. The results support the Resource-Based View (RBV), which suggests that valuable organizational resources and capabilities contribute to competitive advantage and improved performance. The study highlights the importance of strengthening digital competencies, encouraging technology utilization, and fostering innovation among MSMEs to achieve sustainable growth and competitiveness in the digital economy. The findings provide valuable insights for policymakers, business support institutions, and MSME practitioners in designing strategies to improve MSME performance.